GALR1 Methylation in Vaginal Swabs Is Highly Accurate in Identifying Women With Endometrial Cancer. Issue 6 (1st July 2013) - Doufekas, Konstantinos; Hadwin, Richard; Kandimalla, Raju; Jones, Allison; Mould, Tim; Crowe, Susanna; Olaitan, Adeola; Macdonald, Nicola; Fiegl, Heidi; Wik, Elisabeth; Salvesen, Helga B.; Widschwendter, Martin
Abstract : Abstract: Endometrial cancer has become the most common gynecological cancer in developed countries. Postmenopausal bleeding is indicative of the disease in only 1 of 10 women with this symptom. A noninvasive tool to identify women with cancer would be highly desirable. We analyzed more than 27, 000 CpGs in normal endometrial tissue (n = 23) and endometrial cancers (n = 64) and found that DNA methylation of GALR1 is among the most frequent epigenetic alterations in this cancer. We then developed a real-time polymerase chain reaction–based GALR1 methylation test and applied this test to vaginal swabs from 79 women who presented with postmenopausal bleeding. The receiver operating characteristics area under the curve, describing sensitivity and specificity to correctly identify the 41 women with both premalignant and malignant endometrial changes, was 0.93 (95% confidence interval, 0.87–0.97; P < 0.0001). GALR1 DNA methylation is one of the most common molecular alterations in endometrial cancer, and the presence of GALR1 methylation in vaginal swabs from women with postmenopausal bleeding indicates the presence of endometrial malignancy with a sensitivity of 92.7% and a specificity of 78.9%.